CONSTRUCTION OF THE ROTOR AND AIRCRAFT UAVS FOR FLIGHT ALONG A GIVEN TRAJECTORY USING TELEMETRY. COMPARISON OF THE TECHNOLOGIES, BENEFITS AND PROSPECTS FOR USING - Лєнков, С.; Гусак, Ю.; Литвиненко, Н.; Лєнков , Е. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2022)
In this research, the budgetary (no more than $ 120) UAVs of aircraft and rotary types have been designed, that are able to maintain altitude and position, automatically return to the takeoff point on command from the control panel or in case of loss of communication with it, perform automatic flight along a given trajectory and fly with taking into account telemetry data. It has been shown experimentally, that for flight on the mission on airplane to ensure a straight-line flight, it’s advisable to use only a GPS receiver for navigation. The compass setting distorts the plane's straight flight. It was found that in navigation mode, the UAV flight along waypoints, the INAV firmware works more correctly, when the compass is installed in the direction corresponding to the direction of the gyroscopic sensor of the flight controller. Based on the results of flight tests, it was found, that a quadcopter flies waypoints much more accurately, than aircraft. It’s shown, that it’s possible, using the Blackbox INAV 2.5.0 toolkit and the Google Earth Pro service, to form a real flight path of the aircraft and quadrocopter, to determine the speed parameters, and the flight altitude according to the readings of the GPS receiver. The possibility of using 3DR modules for telemetry flight has been established. It’s noted in the work, that for ground stations implemented by INAV Configurator ver.2.5, the Mission Planner for INAV (Android) only MSP protocol works. No automatic switching to LTM protocol detected, that limits telemetry range compared to Ardupilot firmware. The constructed aircraft and quadrocopter can be used to perform photo and video surveys of the terrain in automatic mode with a route length of 6-8 km, using a lithium polymer battery with a capacity of 1500-2200 mAh.

У роботі спроектовані бюджетні (не більше 120$) БПЛА літакового та роторного типів, які в змозі утримувати висоту та позицію, автоматично повертатися в точку зльоту по команді з пульта управління або при втраті зв'язку з ним, виконувати автоматичний політ по заданій траєкторії та політ з обліком даних телеметрії. Експериментально показано, що для польоту місією на літаку для забезпечення прямолінійного польоту доцільно для навігації використання лише GPS приймача. Установка компаса перекриває прямолінійний політ літака. Встановлено, що в режимі навігації, польоті БПЛА по маршрутних точках прошивка INAV коректніше працює при установці компаса в напрямку, що відповідає напрямку установки гіроскопічного датчика польотного контролера. За результатами польотних випробувань встановлено, що квадрокоптер значно точніше пролітає маршрутні точки, ніж літак. Показано можливість за допомогою інструментарію Blackbox INAV 2.5.0 та сервісу Google Earth Pro формування реальної траєкторії польоту літака та квадрокоптера, визначення швидкісних параметрів, висоти польоту за показаннями GPS приймача. Встановлено можливість використання модулів 3DR для польоту телеметрією. У роботі зазначено, що наземних станцій, реалізованих програмами INAV конфігуратор ver.2.5, Mission Planner для INAV (Android) працює лише протокол MSP. Автоматичного перемикання на протокол LTM не виявлено, що обмежує дальність телеметрії в порівнянні з прошивками Ardupilot. Побудовані літак та квадрокоптер можуть застосовуватися для виконання фото та відео зйомок місцевості в автоматичному режимі з протяжністю маршруту 6-8 км при використанні літій полімерної батареї, ємністю 1500-2200 мАг.
КОНСТРУКЦІЯ РОТОРІВ ТА БЕЗПІЛОТНИХ ЛІТАЛЬНИХ АПАРАТІВ ДЛЯ ПОЛІТУ ЗА ЗАДАНОЮ ТРАЄКТОРІЄЮ З ВИКОРИСТАННЯМ ТЕЛЕМЕТРІЇ. ПОРІВНЯННЯ ТЕХНОЛОГІЙ, ПЕРЕВАГИ ТА ПЕРСПЕКТИВИ ВИКОРИСТАННЯ
Keywords: OMNIBUSF4V3; INAV 2.5; GPS receiver; STM32F405; UAV; OSD; ESC controller; Google Earth Pro; MPU6000; Firefly q6; FlySky FS-i6; Failsafe; 3DR; telemetry; OMNIBUSF4V3; INAV 2.5; GPS приймач; STM32F405; БПЛА; OSD; ESC регулятор; Google Earth Pro; MPU6000; Firefly Q6; FlySky FS-i6; Failsafe; 3DR; телеметрія